Binary Organic Solar Cells Breaking 19% via Manipulating the Vertical Component Distribution. Issue 33 (14th July 2022) - Wei, Yanan; Chen, Zhihao; Lu, Guanyu; Yu, Na; Li, Congqi; Gao, Jinhua; Gu, Xiaobin; Hao, Xiaotao; Lu, Guanghao; Tang, Zheng; Zhang, Jianqi; Wei, Zhixiang; et al.
Abstract: The variation of the vertical component distribution can significantly influence the photovoltaic performance of organic solar cells (OSCs), mainly due to its impact on exciton dissociation and charge‐carrier transport and recombination. Herein, binary devices are fabricated via sequential deposition (SD) of D18 and L8‐BO materials in a two‐step process. Upon independently regulating the spin‐coating speeds of each layer deposition, the optimal SD device shows a record power conversion efficiency (PCE) of 19.05% for binary single‐junction OSCs, much higher than that of the corresponding blend casting (BC) device (18.14%). Impressively, this strategy presents excellent universality in boosting the photovoltaic performance of SD devices, exemplified by several nonfullerene acceptor systems. The mechanism studies reveal that the SD device with preferred vertical components distribution possesses high crystallinity, efficient exciton splitting, low energy loss, and balanced charge transport, resulting in all‐around enhancement of photovoltaic performances. This work provides a valuable approach for high‐efficiency OSCs, shedding light on understanding the relationship between photovoltaic performance and vertical component distribution. Abstract : High‐performance binary photovoltaic devices based on D18 and L8‐BO are constructed via manipulating the vertical component distribution in a sequential deposition (SD) process. After tuning the spin‐coating speeds of film deposition, the optimal SD device affords a record power conversion efficiency of 19.05% (certified, 18.9%) for binary single‐junction organic solar cells, much higher than that of the corresponding blend casting device (18.14%).